Utilization of Teaching Space Facilities at Sunyani Polytechnic in Ghana - Quansah, Joseph Yaw Dwamena (Asian Journal of Social Sciences and Management Studies, 2015)
This paper investigates how teaching space facilities were being utilized at Sunyani Polytechnic in the Brong Ahafo Region of Ghana. The essence was to ascertain information on the factors that militate against efficient utilization of teaching space facilities at Sunyani Polytechnic. Descriptive survey research design was adopted for the study. Lottery method of simple random sampling as well as purposive sampling were used in the selection of the sample size of 89 made up of 60 academic staff, 20 senior administrative staff and 9 technicians. Two sets of questionnaire and an interview guide were used for the data collection. The methods used in analyzing the data were frequencies, percentages and cumulative frequencies presented in tables. The key factors identified as constraints to efficient utilization of the teaching space facilities at the Polytechnic were departmentalized time tabling, inadequacy of computer laboratory and small size of instructional rooms. The major recommendations offered include the following: there should be centralized timetabling and computerization of the space allocation, provision of more general computer laboratories and provision of few large instructional rooms for very large class sizes.